ASPEK BISNIS BELAJAR MUSIK DI JAKARTA - Liaw Bun Fa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Music Course has a series of service planning starts from the initial stage of student enrollment up to the last stage of making the results of the student's course results for a month. The following is the flow of services from Chopin Music Course: The first service line begins with the arrival of the consumer to Music Course, Then the consumer approaches the administration desk to simply wander about the classes and levels, the cost for the desired course, the duration of the course, and so on or directly want to register for the course at Chopin Music Course, Then the consumer wants to enroll / his son as a student at Chopin Music Course, Afterwards, Chopin Music Course administrators give blank registration form to be filled by consumers/children who want to enroll as a student at Chopin Music Course, Once the consumer completes the registration form, the administration staff will distribute the payment card for a year. This card as a proof that consumers have made payments for the course money during the month or not, Once consumers get payment cards, consumers can make payments for the month so that the schedule of course sessions directly adjusted according to negotiated agreements between Chopin Music administration officials Course with the consumer, Then the administrative staff make the course schedule arrangement for the consumer, Once completed, the consumer can go back home and come back in accordance with the predefined course schedule. The main segmentation of Music Course are people domiciled in ivory coconut with ages 5 to 19 years who do have hobby and talent in the field of music and parents who want their children to learn music to help educate his thinking. Keywords: Feasibility, BEP, Investment Feasibility, NPV, PI, PP, IRR.